2006
DOI: 10.1007/s11258-006-9182-8
|View full text |Cite
|
Sign up to set email alerts
|

Vertical stratification of vascular epiphytes in submontane and montane forest of the Bolivian Andes: the importance of the understory

Abstract: We studied species richness, composition, and vertical distribution of vascular epiphytes at two sites in the Bolivian Andes. To account for the epiphyte flora on understory trees, epiphytes on shrubs and small trees were sampled in 20 · 20 m 2 subplots around each sampled canopy tree; this understory zone U is introduced as an addition to the well-established five vertical Johansson tree zones. More than 20% of about 500 species recorded were found only in the understory subplots, including ca. 40% of aroids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
145
1
60

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(217 citation statements)
references
References 25 publications
11
145
1
60
Order By: Relevance
“…Although no more than 9% of the recorded species were only found on young trees of the understorey, diversity of dendroid and fan-like species was highest on trunks and understorey trees, and would have been underestimated or neglected when the understorey would have been excluded. The importance of young understorey trees as a habitat for epiphytes was earlier demonstrated for vascular epiphytes by Krömer et al (2007), who found that more than 20% of total species diversity would have been missed when this habitat as well as shrubs would not have been sampled. The results indicate that conservation strategies aimed at preserving the variety of tropical habitats and recognition of suitable indicator species, should consider the understorey trees in addition to the mature canopy trees.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although no more than 9% of the recorded species were only found on young trees of the understorey, diversity of dendroid and fan-like species was highest on trunks and understorey trees, and would have been underestimated or neglected when the understorey would have been excluded. The importance of young understorey trees as a habitat for epiphytes was earlier demonstrated for vascular epiphytes by Krömer et al (2007), who found that more than 20% of total species diversity would have been missed when this habitat as well as shrubs would not have been sampled. The results indicate that conservation strategies aimed at preserving the variety of tropical habitats and recognition of suitable indicator species, should consider the understorey trees in addition to the mature canopy trees.…”
Section: Discussionmentioning
confidence: 86%
“…First, most studies have been carried out in tropical America, and very few in the Old World tropics. Second, almost all epiphyte studies in the natural forest have hitherto focused on mature canopy trees; species on young understorey trees have generally been neglected (Krömer et al 2007). Third, descriptions of vertical distribution patterns have generally been observational; very few studies included statistical analysis of the data (Holz et al 2002;Holz and Gradstein 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A distribuição espacial das epífitas vasculares depende, em grande parte, da variabilidade estrutural dos forófitos (Arévalo & Betancur 2006), especialmente do incremento de tamanho destes (Zotz et al 2001), da qualidade do subosque (Krömer et al 2007), e da complexidade estrutural da floresta (Bennet 1996). Quanto mais complexo o tipo de floresta maior a proporção de forófitos e epífitas (Arévalo & Betancur 2006).…”
Section: Resultsunclassified
“…Nessas zonas o nível de luminosidade é razoavelmente alto, enquanto a presença de bifurcações ou inserção de galhos faz com que haja acúmulo de matéria orgânica, favorecendo a implantação das raízes das espécies epifíticas (Krömer et al 2007); a presença dessa matéria orgânica contribui para a manutenção da umidade, um dos principais fatores limitantes ao epifitismo (Nieder et al 1999, Zotz et al 2001. A presença de todas as famílias nas zonas próximas ao solo (Z1 e Z2) indica que nessa floresta não há restrições de luminosidade para as espécies epifíticas nas zonas mais próximas ao solo (figura 2a), entretanto, é notável a importância da umidade para a sinúsia que ocorre nessas zonas, especialmente pela maior abundância das famílias Orchidaceae e Piperaceae (figura 2b).…”
Section: Resultsunclassified
See 1 more Smart Citation